Lacking a self(ie): "Apps" of desire in virtual Cairo - Revelo La Rotta, Fernando (AUC Knowledge Fountain, 2016)
This project explores through an unconventional assemblage of methods and theories the role of selfies in the contemporary process of subjectivation. Relying on an ethnographic methodology, Lacanian psychoanalysis, and queer theory, this project explore three virtual spaces where selfies live (Instagram, Tinder, and Grindr) and how selfies circulate through the circuits of desire facilitated by the technological interface. The goal of this project is to remind us that there is no essential self and to question such an assumption in any project. Therefore, this project is not invested in discovering the truth about ourselves, the other, or a specific imagined geopolitical construction. Instead, the goal of such an exploration is to take a seemingly banal object, the selfie, that is laden with political signification to see what it has to say about ourselves, as virtual human, and how “we” understand the world. As a result, through this project I invite the reader to delve into a world of ambiguity and to consider the loss of subjectivity not as a destruction of order but as a way to promote new subjectivities and theories based on the loss created by the cut of language on the subject.